Improvement of Audit of Payment in Non-State Non-Profit Organizations (NSNPO) - Khojiyev Mekhriddin Sulaymonovich (Research Parks Publishers, 2022)
Today, non-state non-profit organizations are an integral part of society as an active participant in socio-political processes and gradually occupy a significant place in the public life of the country in the way of building a civil society. Nowadays, the activities of non-state non-profit organizations s in Uzbekistan are primarily aimed at alleviating the social costs of implementing the reform program by creating conditions for protecting the poor, elderly and disabled members of society, expanding employment and professional reorientation of the population, promoting reforms in rural areas and small towns, stimulating development of small and medium-sized businesses. Therefore, this article discusses the solution to the problems of remuneration audit in non-state non-profit organizations (NSNPO) in Uzbekistan. And also, the procedure for auditing the accounting of labor remuneration in non-governmental non-profit organizations is recommended.